Project management BSc-IT,3rd year,6th semester - Gaikwad Rajesh L.,Joshi Bruesh Y., Mascrenhas Romeo S. (Vipul prakashan,Mumbai, 2003)
Computer
Tranfered to BSC-IT Dept., DT.30/7/09
ENGLISH
Keywords: Project management BSc-IT,3rd year,6th semester; Computer; Computer